Tau Ubiquitination in Alzheimer's Disease - Li, Longfei; Jiang, Yanli; Wang, Jian-Zhi; Liu, Rong; Wang, Xiaochuan (Frontiers in Neurology, 2022)
Paired helical filaments (PHFs) from the Alzheimer's disease (AD) brain are highly ubiquitinated and ubiquitination likely plays a vital role in tau filament formation. Whether tau ubiquitination is the causality or consequence of the disease in AD remains elusive. The following questions are worth considering: What does the extent of tau ubiquitination contribute to tau pathology in AD? Does tau ubiquitination influence aggregation or spreading during disease progression? In addition, tau is polyubiquitinated in nerve growth factor-induced PC12 cells and participates in mitogen-activated protein kinase signaling, in addition to its microtubule stabilization function. Therefore, ubiquitination possibly mediates tau signaling under physiological conditions, but tau aggregation in the pathobiology of AD. Here, we review the advancements in tau ubiquitination and the potential therapeutic effects of targeting tau ubiquitination to alleviate tau pathology in AD.